2015
DOI: 10.1038/ncomms8159
|View full text |Cite
|
Sign up to set email alerts
|

The tethering of chromatin to the nuclear envelope supports nuclear mechanics

Abstract: The nuclear lamina is thought to be the primary mechanical defence of the nucleus. However, the lamina is integrated within a network of lipids, proteins and chromatin; the interdependence of this network poses a challenge to defining the individual mechanical contributions of these components. Here, we isolate the role of chromatin in nuclear mechanics by using a system lacking lamins. Using novel imaging analyses, we observe that untethering chromatin from the inner nuclear membrane results in highly deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
216
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(230 citation statements)
references
References 73 publications
10
216
4
Order By: Relevance
“…Schreiner et al 2015) with high-throughput techniques such as chromosome conformation capture and its variants, in which chromatin structure can be reconstructed by sequencing and mapping physically adjacent regions of DNA. Although chromosome conformation capture has the limitation of operating at the scale of millions of cells, and averages out subtle differences between individual cells, it has demonstrated clear and reproducible differences between cell types (Pueschel et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schreiner et al 2015) with high-throughput techniques such as chromosome conformation capture and its variants, in which chromatin structure can be reconstructed by sequencing and mapping physically adjacent regions of DNA. Although chromosome conformation capture has the limitation of operating at the scale of millions of cells, and averages out subtle differences between individual cells, it has demonstrated clear and reproducible differences between cell types (Pueschel et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Schreiner et al (2015) in the fission yeast Schizosaccharomyces pombe showed the effect of chromatin flow on the rigidity of the nucleus. S.pombe lacks lamins, and thus has a flexible nucleus which can be studied outside the influence of the lamin proteins.…”
Section: Nuclear Shape From Withinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the tethering of chromatin to the nuclear periphery has an important role in the chromatin flow by defining changes in nuclear shape (34). We could raise the hypothesis that cholesterol might trigger chromatin structural changes that may contribute to the intra-nuclear organization of chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it houses the chromosomes, which behave very differently from other macromolecular complexes due to the sheer size of the chromatin polymer. These different attributes make the nucleus very interesting from its basic biophysical properties on up (4). I then became fascinated with understanding why the nuclear envelope doesn’t simply tubulate in response to cytoskeletal forces (like the ER does).…”
mentioning
confidence: 99%